Shariah non-compliance risk and its effects on Islamic financial institutions - Hassan, Rusni (International Islamic University Malaysia, 2016)
The objective of this paper is to provide the definition of shariah non-compliance risk associated with Islamic financial institutions (IFIs). Having a precise definition of shariah non-compliance risks is highly necessary for the purpose of developing a comprehensive risk management framework for an Islamic financial system. This study is conducted through a literature review on Islamic turath, regulatory provisions and existing academic journals on Islamic risk management. This paper provides an in-depth discussion on the major elements that trigger shariah non-compliance risks and hence affects the validity of Islamic contracts such as riba, gharar, taghrir, ghubn, etc. These elements of risk were identified as that emerging from the entire process of developing an Islamic financial product, starting from the structuring stage until the execution of the product in the market and hence cause severe both financial and non-financial costs to IFIs. This research may have some implications to the Islamic finance industry in Malaysia, becoming a reference for Malaysian IFIs in structuring their own comprehensive risk management and internal control system and hence enhance the effectiveness of the shariah governance practice within the IFIs.